PSV-22 The effects of flavoring agents on feeding behavior, feed efficiency, growth performance and temperament of newly arrived feedlot cattle. (30th November 2020) - Ahmad, Mustaq; Moya, Diego; Johnson, Jordan A; Penner, G; Blanch, Marta; Seddon, Yolande
Abstract: Ninety steers (259.9 ± 36.18 kg BW) were used in a 56-d experiment to assess the effects of flavoring additives on feeding behavior, feed efficiency, growth performance, and temperament of newly arrived feedlot cattle. Steers were homogenously distributed by BW into six pens (15 head/pen) and pen was randomly assigned to one of 3 treatments (2 pens/treatment): a standard feedlot receiving diet (CT); or the same diet with a flavoring additive comprised of either sweeteners (SW) or a mix of basic tastes (MX) at 1 g/kg (Lucta SA, Barcelona, Spain). Pens were equipped with a feed intake monitoring system (Growsafe Systems, Airdrie, Canada), while BW and chute exit flight speed were measured bi-weekly during the study. Data were analyzed using a mixed-effects model accounting for repeated measures. There were multiple treatment × time interactions (P < 0.05), where DMI per meal was greater in SW than CT and MX on wk 3 and 5, respectively, and in MX than CT and SW on wk 3 and 7, respectively. The number of visits to the feed bunk per day was greater in MX than CT on wk 2, it was greater in SW than MX on wk 4, and it was greater in CT than in MX and SW on wk 4, and wk 7 and 8, respectively. The eating rate was greater in SW than MX on wk 4 and 5 and greater than CT and on wk 4. Although the cumulative responses for DMI, ADG and feed efficiency (FE; kg BW/kg DM) were not significant (P > 0.1), FE was greater in SW and MX than CT from 27 to 41 d. Despite these positive effects on FE, there was no feeding pattern associated with the inclusion of flavoring additives in the diet of receiving feedlot cattle.